2012
DOI: 10.1021/jp2104837
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Water in the Heterogeneous Uptake of Glyoxal by Mixed Glycine and Ammonium Sulfate Aerosols

Abstract: This study focuses on the heterogeneous reactions of gas phase glyoxal with aerosols of glycine, the most abundant amino acid in atmospheric aerosols, as well as with a mixture of glycine and ammonium sulfate (AS) at a molar ratio of 1:100 (glycine-AS 1:100). Aerosols were exposed to varying relative humidity (RH) conditions in the presence of gas phase glyoxal for ∼1 h, followed by drying and efflorescence. The changes in size, chemical composition, and optical properties were consequently measured. The react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 63 publications
6
84
0
1
Order By: Relevance
“…Figure 1 shows the distribution of the real parts of biomass burning (Westphal et al 1991;Yamasoe et al 1998;von Hoyningen-Huene et al 1999;Guyon et al 2003;Procopio et al 2003;Colarco 2004;Schkolnik et al 2007;Hungershoefer et al 2008;Levin et al 2010), and organic (Schnaiter et al 2003;Pettersson et al 2004;Lack et al 2006;Abo Riziq et al 2007;Barkey et al 2007;Yu et al 2008;LangYona et al 2009;Wex et al 2009;Lang-Yona et al 2010b;Nakayama et al 2010b;Trainic et al 2011;Flores et al 2012;Trainic et al 2012) and inorganic (Abo Riziq et al 2007;LangYona et al 2009;Trainic et al 2011) aerosols found in the literature. In this study, we exclude soot particles due to their complex aggregated structure.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the distribution of the real parts of biomass burning (Westphal et al 1991;Yamasoe et al 1998;von Hoyningen-Huene et al 1999;Guyon et al 2003;Procopio et al 2003;Colarco 2004;Schkolnik et al 2007;Hungershoefer et al 2008;Levin et al 2010), and organic (Schnaiter et al 2003;Pettersson et al 2004;Lack et al 2006;Abo Riziq et al 2007;Barkey et al 2007;Yu et al 2008;LangYona et al 2009;Wex et al 2009;Lang-Yona et al 2010b;Nakayama et al 2010b;Trainic et al 2011;Flores et al 2012;Trainic et al 2012) and inorganic (Abo Riziq et al 2007;LangYona et al 2009;Trainic et al 2011) aerosols found in the literature. In this study, we exclude soot particles due to their complex aggregated structure.…”
Section: Approachmentioning
confidence: 99%
“…To choose the appropriate range for size parameters, we investigated the Q ext standard deviations (SDs) from measurements done in this study and from studies found in the literature (Pettersson et al 2004;Lack et al 2006;Abo Riziq et al 2007;Dinar et al 2008;Butler et al 2009;Lang-Yona et al 2009Miles et al 2010a, b;Nakayama et al 2010a;Trainic et al 2011;Flores et al 2012;Trainic et al 2012). The average Q ext SD in all datasets did not exceed 0.075.…”
Section: Approachmentioning
confidence: 99%
“…Earlier work has reported the formation of a monolayer of adsorbed water on the surface of solid AS at 60 % relative humidity (RH) (Romakkaniemi et al, 2001). Surface-adsorbed water plays a potential role in facilitating the heterogeneous chemistry of atmospheric aerosols (Trainic et al, 2012;Chu and Chan, 2017). Yet the relative role of surface chemistry and bulk processes is poorly understood due to the lack of surface-sensitive techniques available for studying individual atmospheric particles (Ault et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups have used Aerosol CRDS (A-CRDS) to probe internal and external particle mixing Freedman et al 2009;Khalizov et al 2009;Lack et al 2009;Radney et al 2009;Attwood and Greenslade, 2012), effects of relative humidity (Beaver et al 2008;Attwood and Greenslade, 2012;Brem et al 2012;Trainic et al 2012) and particle reactivity (Lu et al 2011;Zarzana et al 2012). Agreement between extinction cross section measurements and those calculated with Mie theory is often promising, typically on the order of 2-12 % (Pettersson et al 2004;Baynard et al 2007;Riziq et al 2007;Freedman et al 2009;Lang-Yona et al 2009;Radney et al 2009;Miles et al 2010b;Li et al 2011;Mellon et al 2011).…”
Section: Introductionmentioning
confidence: 99%